ChemInform Abstract: Coordination Polymers for Energy Transfer: Preparations, Properties, Sensing Applications, and Perspectives. Issue 49 (December 2015) - Zhang, Xuanjun; Wang, Wenjing; Hu, Zhangjun; Wang, Guannan; Uvdal, Kajsa
Abstract: Review: 190 refs.